Height, Health and History: Nutritional Status in the United Kingdom, 1750-1980 - Eltis, David (Labour / Le Travail, 1991)
The article reviews the book, "Height, Health and History: Nutritional Status in the United Kingdom, 1750-1980," by Roderick Floud, Kenneth Wachter & Annabel Gregory.
Keywords: BOOKS -- Reviews; FLOUD, Roderick; GREGORY, Annabel; HEIGHT, Health & History: Nutritional Status in the United Kingdom, 1750-1980 (Book); Nonfiction; Nutrition; WACHTER, Kenneth